ANALISIS KUALITAS PELAYANAN PUBLIK PAJAK HOTEL DAN RESTORAN PADA BADAN PELAYANAN PAJAK DAERAH KOTA MALANG - Syafriel, Muhammad; Roziq, Mohammad (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2024)
This research is intended to analyze and evaluate the public service quality as perceived by the hotel and restaurant’s taxpayers at the tax office in Malang City. We compare the perceived public service quality of tax officials to the expected public service quality of taxpayers. The data was gathered from 88 hotels' and 80 restaurant’s taxpayers at the tax's services office in Malang City. The gap analysis was conducted to assess the difference between the perceived and expected public service quality of the respondents, which represents the quality of public service. The results of the research show that the users of public services are very satisfied with all services obtained from the Malang Regional Tax Service Agency. This is evidenced by 21 service’s indicators, the average of the obtained values is categorized as good or very good. On the other hand, public service providers are also required to be more creative and innovative in providing services to the public. The current dynamics of society that tend to be more critical must be addressed positively so that the expectations of services and the degree of importance of services can be simultaneously fulfilled and create reliable and quality public services.